The Effect Of Fiscal Decentralization On Regional Economic Growth Andi Kurniawan1, Fajar Rezeki Ananda Lubis2, Syaifuddin3 - Andi Kurniawan; Fajar Rezeki Ananda Lubis; Syaifuddin (Cita konsultindo, 2026)
This study aims to analyze the impact of fiscal decentralization on regional economic growth in Indonesia. The method used is a literature approach by studying various sources. The research focuses on four things: (1) the basic concept of fiscal decentralization, (2) the impact of fiscal decentralization on regional economic growth, (3) factors influencing the effectiveness of fiscal decentralization, and (4) the relationship between fiscal decentralization and regional development strategies. Data sources were obtained from books, journals, government reports, and related policy documents. The research findings indicate that fiscal decentralization generally has a positive impact on regional economic growth, especially in regions with a high level of financial independence and a sound cash management system. Regions that are able to optimally collect local revenue can increase investment, create jobs, and strengthen productive sectors. However, this impact is not evenly distributed due to persistent disparities between regions, a lack of human resource capacity in the apparatus, and dependence on funds provided by the central government. Overall, fiscal decentralization is an important tool in strengthening regional economies, but its success depends heavily on financial management methods, institutional capabilities, and the commitment of local governments to managing public resources effectively and responsibly.